PROBIOTIC DEVELOPMENT OF ACID BACTERIA OF LUBRICATED POTENTIAL WASTE REDUCING CHICAGEN CHOLESTEROL BEHAVIOR BROILER STRAIN HABBART - Astuti Astuti (Jurnal Penelitian Saintek, 2010)
The aims of rhis research is to  .\/reptococcus thermophillus  .from  .fintl thc in.fluence of gifing lsctlate probiotic B,4L The.fish waste trn'ard the broilers'  cind the degree Oj bt"oilers't'holesterol. The research matertals iu'e  qppearance of wool ."/()  roosters oi broiler Sn'ain Lohntttnn, produclion of PT \v{ilii Breeder Adirama at theage of I tt,eek. The probiotic ttJ isolate tt'eatmeill of Lacture,lcid Bqcteria (BAL) whichis used in this research is Streptococcusthernrcphillus bacteria in  .from  of  Jt  eeze Cying tthich contes lj'om llutrition Biochemical Laboratory, Vete.rinary Faculry of UGfut. The treatrnentI isas the control (u'ithctrtt  BAL), the rumther o/ BAL in treatment II i.s 106 CFUhnl, the rnunberofBALintreatmentlllisl0 CF'Lt,'rnl,thentttnberafBALintreatmentlVisl0s CFLI/wl. The data collection  Jitr  the degree of cholesterol is done aJier 28 days. The data which is collected of woo{and the degree of broilers'cholesterol. The research result; lhe treatment of giving lactate trcid bac:teria o.f Streptococctrs thermophillus caused the decrease ofthe degree ofbroilers'cholesterol signilicantll, dnd the best level ofB.4L is I 0^ C FL':nrl